Sound-Induced Flash Illusions Support Cortex Hyperexcitability in Fibromyalgia - Vincenzo Di Stefano; Salvatore Iacono; Andrea Gagliardo; Bruna Maggio; Giuliana Guggino; Massimo Gangitano; Roberto Monastero; Vito Renato Maggio; Nadia Bolognini; Filippo Brighina (Pain Research and Management)
Objectives. Fibromyalgia (FM) is characterized by spontaneous chronic widespread pain in combination with hyperalgesia to pressure stimuli. Sound-induced flash illusions (SIFIs) reflect cross-modal interactions between senses allowing to assess a visual cortical hoerexcitability (VCH) by evaluating the fission and fusion illusions disruption. The aims of the present study were to explore whether SIFIs are perceived differently in patients with fibromyalgia as compared to healthy controls (HCs) and how migraine affects fission and fusion illusions in fibromyalgia. Methods. A single flash (F) accompanied by 0 to 4 beeps (B) was presented to induce the fission illusion while multiple flash (i.e., 2 to 4) accompanied by 0 or 1 beep was presented to induce fusion illusion. The mean number of perceived flashes in fission and fusion illusion trials was compared between the groups (i.e., FM, FM with migraine, and HCs) using repeated-measures analysis of variance. Medication history was recorded along with the administration of Fibromyalgia Impact Questionnaire and Hospital Anxiety and Depression scales. Results. Twenty-four patients with FM (mean age 51, 2 ± 10, 6 years; 22 females), seventeen patients with FM and migraine without aura (mean age 47.8 ± 11.4 years; 16 females; 13 chronic, 4 episodic migraine), and forty-one age- and sex-matched HCs (mean age 47.3 ± 6.9 years; 34 females) participated in the study. Fission and fusion illusory effects were detected in all the participants. However, in FM patients, the fission illusion was reduced and almost abolished as compared to HCs (1F1B, p=0.02; 1F2B, p<0.0001; 1F3B, p<0.0001; 1F4B, p=0.0001), while there were no differences between groups in fusion trials. Migraine did not affect the fission and the fusion illusions. Conclusion. Results from this study confirm that patients with FM have a VCH suggesting that the pathological changes in cortical excitability might have important roles in the pathophysiology of FM. SIFI represents a noninvasive behavioral tool for the exploration of cross-sensory functional interplay.